Utilization of Visual Media in Overcoming Reading Delays Among 2nd Grade Elementary School Students - Ahmad Ahmad; Ridwan Andi Mattoliang; Nur Rahmi; Dedi Harianto (PT. Global Research Collaboration, 2025)
Reading skills are fundamental abilities that are essential in the learning process, especially for elementary school students. However, reading delays remain one of the main problems faced by 2nd-grade students at UPT SBF SD Negeri Panaikang III. This community service program aims to address reading delays through the utilization of visual media as a teaching aid. The program is implemented in stages, including problem identification, planning, activity execution, evaluation, and follow-up actions. Interventions are carried out using visual media, such as illustrated flashcards, posters, and picture storybooks, designed to enhance students' interest, motivation, and reading skills. Mentoring activities are conducted individually and in small groups, involving teachers and parents to support the learning process. Evaluations are conducted through direct observation, discussions with teachers, and interviews with students and parents. The program results indicate that the use of visual media significantly improves students' reading abilities. In conclusion, the utilization of visual media is effective in addressing reading delays among 2nd-grade students and provides positive impacts on their psychological and social aspects. It is recommended that this method be implemented sustainably and further developed to improve the quality of reading instruction at the elementary school level through collaboration between schools, teachers, and parents.